POLA ASUH ORANG TUA DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI MASA PANDEMI - Navida, Ilyun; Fakhriyah, Fina; Kironoratri, Lintang (Jurnal Ilmiah Bina Edukasi, 2021)
This study aims to explain the role of parenting in improving the learning motivation of grade VI students of SD 1 Rejosari during the pandemic.The research method used is mixed methods research. Data collection techniques include observation,interview and questionnaires,documentation, and the results of fields notes. The data analysis techniques used were interview and questionnaries. The results showed that: (1) parents of subject 1 applied permissive parenting and children’s learning motivation was in the low category, parents of subject 2 applied democratic parenting and children’s learning motivation was in high category, while parents of subject 3 applied permissive parenting and children’s learning motivations falls into the low category. (2) The supporting factors for parenting parents in increasing student motivation during the pandemic are in the form of parental attention in various ways for each child, while the inhibiting factors are parents, activities such as work and children’s conditions such as playing with peers, playing handphone, and, watching tv.